The state and prospects of development of national higher pharmaseutical education - T. D. Reva; I. V. Nizhenkovska; O. M. Chkhalo; N. V. Stuchynska (Medičnì Perspektivi)
The paper considers the materials of the Pharmacists Summit and International Pharmaceutical Congresses, in particular, the issue of achieving quality pharmaceutical education. It shows cause of the proper training process of pharmacy sector specialists in accordance with current state and requirements of the society and suggests a model of professional pharmaceutical education. According to the authors of the paper, the implementation of education quality in Ukraine calls for, first, professionally educated personnel in the pharmacy sector of healthcare; second, proper academic and university infrastructure for training future specialists within the system of higher pharmaceutical education; third, ensuring the high quality of higher pharmaceutical education on the basis of implementing the competence approach and taking into account international experience on pharmacy development. Increasing significance of the pharmacy branch in Ukraine is directly linked to the quality of training of pharmacy specialists, continuous improvement of the content of their education, implementation of new educational technologies, adapting higher pharmaceutical education to European standards. According to the authors, an important condition of ensuring effective professional training of future pharmacy specialists within the national system of higher pharmaceutical education is the following: firstly, considering public demand to the level of healthcare services, disease prevention; secondly, implementing the productive global experience on introducing customer service standards. The established prospects of the development of national higher pharmaceutical education include: 1) the adoption of ethical principles of training Masters of Pharmacy within the system of higher pharmaceutical education; 2) focus on European pharmacy standards which are based on high customer service standards; 3) improvement of the content of pharmacy specialist education taking into account the development of national pharmaceutical production; 4) ensuring the development of the clinical direction within the system of general pharmacist training.